Underwater Acoustic Power Around Submerged Body in Shallow Water Using Boundary Element Method - M. Fatkhurrozi; Irsan S. Brodjonegoro (Journal of Engineering and Technological Sciences, 2019)
Underwater acoustic power around a submerged body in shallow water was investigated using the Boundary Element Method (BEM). The model domain simulated a nearshore environment with shallow water conditions. The seabed was assumed flat and sound velocity was constant over depth. The boundary element method was combined with eigenfunction expansion to model radiation boundary conditions. Underwater acoustic power was calculated from the underwater acoustic potential in the domain. Several cases were investigated in this study: cases with variation of submerged body distance from the seabed, variation of submerged body location from the underwater acoustic source, and variation of submerged body length.